2007
DOI: 10.1103/physrevlett.98.064801
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Ion-Induced Electronic Desorption of Gas from Metals

Abstract: During heavy-ion operation in several particle accelerators worldwide, dynamic pressure rises of orders of magnitude were triggered by lost beam ions that bombarded the vacuum chamber walls. This ioninduced molecular desorption, observed at CERN, GSI, and BNL, can seriously limit the ion beam lifetime and intensity of the accelerator. From dedicated test stand experiments we have discovered that heavy-ion-induced gas desorption scales with the electronic energy loss (dE e =dx) of the ions slowing down in matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Measurements have shown that energetic heavy ions striking walls at any angle from normal to grazing incidence will desorb copious amounts of gas [3,27,28]. We have measured the velocity of desorbed gas, and found that it corresponds to wall-temperature hydrogen, which is consistent with residual gas measurements that hydrogen is the dominant desorbed species after an ion pulse.…”
Section: Issue: Reduce Gas-induced Beam Loss and Degradation To Neglisupporting
confidence: 79%
See 2 more Smart Citations
“…Measurements have shown that energetic heavy ions striking walls at any angle from normal to grazing incidence will desorb copious amounts of gas [3,27,28]. We have measured the velocity of desorbed gas, and found that it corresponds to wall-temperature hydrogen, which is consistent with residual gas measurements that hydrogen is the dominant desorbed species after an ion pulse.…”
Section: Issue: Reduce Gas-induced Beam Loss and Degradation To Neglisupporting
confidence: 79%
“…Electron emission decreases by factors ~20 from grazing to normal incidence, whereas desorption scales as a fractional power of 1/cos, decreasing by factors 2-3 over the same range of angles [27,28]. Both electron emission and gas desorption are minimized for impact near 0°, i.e., normal incidence and scale with the electronic component of ion energy loss in matter dE e /dx [2,3]. Gas will cause charge exchange (K + → K 0 ) and ionization (K + → K ++ or higher ionization states); ions that change charge will hit the beam tube in a long accelerator.…”
Section: Issuementioning
confidence: 99%
See 1 more Smart Citation
“…For desorption processes (i.e. release of material in the gas phase) a slope α of two has been reported (Molvik et al 2007;Dartois et al 2015). Figure 8 gives the material modification rates as a function of the column density for the two different values of α for the two initial CR spectrum, E −1 and SP68.…”
Section: Structural Modification and Desorption From Large Grainsmentioning
confidence: 99%
“…Copious electrons are generated by slamming the beam onto the end plate. We study electron effects in the magnetic section, which is heavily instrumented with diagnostic devices and suppressor electrodes dedicated to the various measurements of electron flux, electron energy spectrum, and gas analysis [26][27][28][29][30][31][32]. The primary electrons created at the end plate propagate upstream, entering only two quadrants of the fourth (last) magnet because of the sign of E × B.…”
Section: The High Current Experimentsmentioning
confidence: 99%